Approximation by an iterative method of a low‐Mach model with temperature dependent viscosity. (29th October 2018) - Calgaro, Caterina; Colin, Claire; Creusé, Emmanuel; Zahrouni, Ezzeddine
Abstract : In this work, we prove the existence and the uniqueness of the strong solution of a low‐Mach model, for which the dynamic viscosity of the fluid is a given function of its temperature. The method is based on the convergence study of a sequence towards the solution, for which the rates are also given. The originality of the approach is to consider the system in terms of the temperature and the velocity, leading to a nonlinear temperature equation and the development of some specific tools and results.